The Influence of Leadership, Motivation, And Job Satisfaction On Employee Performance (Survey at PT Karya Indah Lestari, Berau Regency, Kalimantan) - Fitriah Agustika; Kosasih, Kosasih; Farida Yuliaty; Vip Paramarta; Sobarna Kartamiharja (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Abstract: Starting from the emergence of a phenomenon that shows signs of decreasing work efficiency, employee satisfaction, and employee loyalty to the company since the Covid 19 pandemic, so interested in conducting this research. This study aims to obtain empirical evidence of the influence of leadership, motivation, and job satisfaction on employee performance at PT Karya Indah Lestari, Berau Regency, East Kalimantan. The research method used is descriptive verification analysis and multiple linear regression analysis. Data collection using questionnaires distributed to all employees using proportional random sampling techniques. The number of respondents collected was 85 people representing all employees working at PT Karya Indah Lestari, Berau Regency, East Kalimantan, who were selected randomly. The results of the descriptive analysis show that leadership, motivation, job satisfaction and employee performance are generally classified as very good. The results of the verification analysis, both partially and simultaneously, prove that leadership, motivation and job satisfaction have a positive and significant effect on employee performance, so the researcher suggests that they be maintained and improved further.